Melatonin Treatment Delays the Senescence of Cut Flowers of “Diguan” Tree Peony by Affecting Water Balance and Physiological Properties - Mengdi Wu; Peidong Zhang; Yuke Sun; Wenqian Shang; Liyun Shi; Shuiyan Yu; Songlin He; Yinglong Song; Zheng Wang (Horticulturae)
Tree peony (Paeonia suffruticosa Andr.), which is a traditional flower cultivated in China, is rapidly becoming an important species in the cut flower industry. Thus, extending the vase life of tree peony cut flowers is a major goal in the cut flower industry. Melatonin, which is a new type of antioxidant, plays an important regulatory role in the preservation of cut flowers. Therefore, this study employed the cut flower of tree peony “Diguan” as the test material to investigate the preservative effects of the antioxidant melatonin on the cut flower of tree peony “Diguan”. We examined tree peony cut flowers in terms of their morphology, lifespan, relative fresh weight, relative diameter, and water balance value after treatments with different melatonin concentrations (0.2, 0.3, 0.4, and 0.5 mg·L−1) to select the optimal treatment concentration. Considered together, these analyses clarified the effects of melatonin on the preservation of “Diguan” tree peony cut flowers. Specifically, the exogenous application of melatonin positively affected the preservation of tree peony cut flowers by improving the water balance value and increasing the soluble protein content and antioxidant enzyme activities, thereby prolonging the ornamental period of tree peony cut flowers. The fresh weight of flower branches is significantly positively correlated with soluble protein, and cut flower lifespan increases with the values of soluble protein and the fresh weight of flower branches, with a large correlation coefficient. It can be used as an important indicator to measure cut flower lifespan in subsequent research. The 0.4 mg L−1 melatonin treatment was optimal for preserving tree peony cut flowers because of its positive effects on the duration of the ornamental period and ornamental quality.